Ankle Pump Exercise and Foot Massage Intervention on Reducing Leg Edema in Chronic Kidney Disease (CKD) Patients - Rondhianto; Alya 'Izzatur Rohmah; Mustakim; Jon Haffan Sutawardana (KHD Production, 2025)
Chronic Kidney Disease (CKD) is a significant health problem with increasing prevalence, characterized by a progressive decline in kidney function resulting in fluid accumulation in the body. One common clinical manifestation is edema in the lower extremities. Ankle pump exercises and foot massage are non-pharmacological interventions that can help reduce edema by improving venous and lymphatic circulation. This study aims to analyze the implementation of nursing care in relation to the effect of ankle pump exercise and foot massage on reducing leg edema in patients with chronic kidney disease (CKD). This study used a case study design with a nursing care approach in a CKD patient with edema in the Anturium Ward of Dr. Soebandi Regional General Hospital, Jember. Ankle pump exercises were performed for 10 minutes, followed by a 15-minute foot massage, which was repeated for three consecutive days of treatment. The degree of edema was evaluated using the edema pitting scale before and after the intervention. The results showed a decrease in edema from +2 to +1 (1 mm in the left leg) and from +1 to 0 (2 mm in the right leg). There was also a decrease in ankle circumference of 20 cm and instep of 25.5 cm on the right leg, and 19 cm at the ankle and 23.7 cm at the left leg. Furthermore, muscle strength increased from 2 cm to 5 cm in the left leg and from 1 cm to 4 cm in the right leg. Ankle pump exercises and foot massage effectively reduce edema in CKD patients. This therapy can be used as an independent nursing intervention to enhance the quality of life for patients with CKD who experience edema.